2023
DOI: 10.1001/jamapsychiatry.2023.2983
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Antidepressants in Patients With Comorbid Depression and Medical Diseases

Ole Köhler-Forsberg,
Victoria Stiglbauer,
Jelena Brasanac
et al.

Abstract: ImportanceEvery third to sixth patient with medical diseases receives antidepressants, but regulatory trials typically exclude comorbid medical diseases. Meta-analyses of antidepressants have shown small to medium effect sizes, but generalizability to clinical settings is unclear, where medical comorbidity is highly prevalent.ObjectiveTo perform an umbrella systematic review of the meta-analytic evidence and meta-analysis of the efficacy and safety of antidepressant use in populations with medical diseases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 93 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…The findings also suggest that pharmacotherapy of MDD is safe for the short-term treatment of MDD. This is consistent with previous findings ( 1 ). On the other hand, from the long-term perspective, the psychoeducation gains importance as a tool to improve the overall functioning, adherence to treatment, and relapse prevention.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The findings also suggest that pharmacotherapy of MDD is safe for the short-term treatment of MDD. This is consistent with previous findings ( 1 ). On the other hand, from the long-term perspective, the psychoeducation gains importance as a tool to improve the overall functioning, adherence to treatment, and relapse prevention.…”
Section: Discussionsupporting
confidence: 94%
“…The treatment of depression is multifaceted and usually involves a combination of pharmacological and non-pharmacological interventions. Nowadays, antidepressant treatment is effective, safe, and available ( 1 ). Yet, it is time-consuming, financially challenging, and human demanding.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have reported that conventional depression treatments, both medications and psychotherapy, had medium effect sizes in people with chronic medical illness (SMD for antidepressants vs placebo, 0.42 [95% CI, 0.30-0.54]; SMD for psychotherapy vs no psychotherapy, 0.62 [95% CI, 0.52-0.79]), people who have experienced childhood trauma (SMD for antidepressants or psychotherapy vs placebo or no psychotherapy, 0.61 [95% CI, 0.29-0.92]), and those recently bereaved (SMD for psychotherapy vs no psychotherapy, 0.35 [95% CI, 0.08-0.62]) …”
Section: Discussionmentioning
confidence: 99%
“…Next, to prevent duplication of data, a matrix containing all eligible systematic reviews/meta-analyses for each category of mental disorder was created. Where there were multiple eligible systematic reviews/meta-analyses for the same disorder and treatment, we preferentially included meta-analyses, and if multiple eligible meta-analyses remained, then we included the one containing the largest number of studies for the same disorder and treatment, in line with recent umbrella reviews [46,47].…”
Section: Methodsmentioning
confidence: 99%